Challenges on the road to a multicellular bioartificial liver. (31st May 2017) - Starokozhko, Viktoriia; Groothuis, Geny M.M.
Abstract: Over recent years, the progress in the development of a bioartificial liver (BAL) as an extracorporeal device or as a tissue engineered transplantable organ has been immense. However, many important BAL characteristics that are necessary to meet clinical demands have not been sufficiently addressed. This review describes the existing challenges in the development of a BAL for clinical applications, highlighting multicellularity and sinusoidal microarchitecture as crucial BAL characteristics to fulfil various liver functions. Currently available sources of nonparenchymal liver cells, such as endothelial cells, cholangiocytes and macrophages, used in BAL development are defined. Also, we discuss the recent studies on the reconstruction of the complex liver sinusoid microarchitecture using various liver cell types. Moreover, we highlight some other aspects of a BAL, such as liver zonation and formation of a vascular as well as biliary network for an adequate delivery, biotransformation and removal of substrates and waste products. Finally, the benefits of a multicellular BAL for the pharmaceutical industry are briefly described. Copyright © 2016 John Wiley & Sons, Ltd.